Chafing behaviour from two carcharhinid shark species Carcharhinus falciformis and C. galapagensis on whale sharks Rhincodon typus - Pancaldi, Francesca; Becerril-García, Edgar Eduardo; Higuera-Rivas, Jesús Erick (Revista de Biología Marina y Oceanografía, 2022)
This report provides observations regarding chafing interactions from two carcharhinid species, the silky shark, Carcharhinus falciformis and the Galapagos shark, C. galapagensis, on whale sharks, Rhincodon typus, in the Revillagigedo National Park, Mexico. Four events were observed between 2013 and 2019 by means of SCUBA diving and drone aerial surveys. These interactions appeared to be casual and triggered by the large dimensions and slow swimming speed of the whale sharks.